Urban governance in Istanbul - Uzun,Nil (2010)
Urban governance has been an important issue since the 1980s, as have the effects of globalisation on urban policies. Although no consensus exists on a definition of governance, it is possible to state that it expresses a shift in the roles of formal government structure, and especially the change in the sharing of responsibilities between the public, private, voluntary, and household spheres. Turkey has also been experiencing the effects of globalisation, and there is an ongoing restructuring process within which government structures are moving toward governance. The goal of this paper is to present a critical evaluation of urban governance. This will be done with the focus on whether the concept of urban governance can explain the urban management model in countries on the periphery. The case of Istanbul is used as an example for this discussion.